2016
DOI: 10.1039/c6cy00544f
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen-doped porous carbon materials: promising catalysts or catalyst supports for heterogeneous hydrogenation and oxidation

Abstract: Developing novel and efficient catalysts is a critical step in common heterogeneous hydrogenation and oxidation reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
133
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 274 publications
(133 citation statements)
references
References 189 publications
0
133
0
Order By: Relevance
“…The research results have demonstrated that the incorporation of nitrogen (N) in the carbon skeleton may result in charge modulation to tune their chemical and electrical activities, and thus further promote their catalytic activity. [29] Different strategies have been developed for the preparation of nitrogen doped porous carbon materials, such as post modification, direct carbonization of N-containing precursors or mixture of nitrogen source and carbon source, [30] hardtemplate method and soft-template method. [25] Moreover, the doped nitrogen may increase the binding energy of carbon-metal and stabilize the deposited metal nanoparticles with small size, which can enhance the catalytic capability and durability of the resulting heterogeneous catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…The research results have demonstrated that the incorporation of nitrogen (N) in the carbon skeleton may result in charge modulation to tune their chemical and electrical activities, and thus further promote their catalytic activity. [29] Different strategies have been developed for the preparation of nitrogen doped porous carbon materials, such as post modification, direct carbonization of N-containing precursors or mixture of nitrogen source and carbon source, [30] hardtemplate method and soft-template method. [25] Moreover, the doped nitrogen may increase the binding energy of carbon-metal and stabilize the deposited metal nanoparticles with small size, which can enhance the catalytic capability and durability of the resulting heterogeneous catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the support is also a non‐negligible factor affecting the yield of CMO. Carbon materials have been testified to be one of the best choices as the catalyst support for heterogeneous reactions in the liquid phase owing to their excellent mechanical strength and stability under hydrothermal conditions, good electronic properties, large surface area for dispersing active components, easy recovery–refining–recycling for precious metals, relatively low cost as well as versatile existing forms . Over the past years, various carbon‐supported Pt (Pt/C) catalysts, including Pt/carbon nanotubes (CNTs), Pt/graphite, Pt/graphene, Pt/carbon nanofibers, Pt/carbon aerogel and xerogel, Pt/mesoporous carbon, and Pt/hollow carbon spheres, have been investigated for hydrogenation of CMA towards CMO.…”
Section: Introductionmentioning
confidence: 99%
“…Up to date now, with combination of the effective synthesis strategies and renewable biomass, great progresses have been made in the application field of catalysis, adsorption/separation, energy conversion and storages. Several groups have summarized the recent progresses of biomassderived carbon in catalysis, [20][21][22] rechargeable lithium/sodium batteries, 23 and Song et al also gave a brief introduction of preparation and applications of crude biomass. 24 Besides the large roles in those important fields, biomass-derived carbons are also something in energy application (energy conversion and storage in electrochemical application).…”
Section: Introductionmentioning
confidence: 99%